ABUSE OF AUTHORITY BY THE REGIONAL GOVERNMENT FOR THE CONSTRUCTION OF NATIONAL ROADS - Ahmad Munir; Luthfie Octavian; Sugiran Try Wibowo; Bagus Teguh Santoso (Universitas Muhammadiyah Tangerang, 2023)
Roads as one of the transportation infrastructure are important elements in building the life of the nation and state. The government has an important role in providing investment for road construction in accordance with its authority as regulated in Law Number 2 of 2022 on the Second Amendment to Law Number 38 of 2004 concerning Roads. However, there are district governments carrying out the construction of national roads which should be the authority of the central government. This writing uses a normative research method with a statutory approach and a conceptual approach related to regulations and regulatory concepts over the authority of local governments in the construction of national roads. Besides that, it uses a conceptual approach , namely the approach taken to the concept of regional government authority in road construction . The purpose of this study is to analyze the abuse of authority by the Regional Government for the construction of National Roads. The results of the study stated that the Regency/City Regional Government carried out the construction of national roads , The regency /city regional government fulfills the element of abusing authority or exceeding authority . For this reason, the central and regional governments can carry out road construction, but this must be in accordance with their respective authorities.